2008
DOI: 10.1111/j.1532-849x.2008.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a High Fracture Toughness Composite Ceramic for Dental Applications

Abstract: Despite the promising mechanical properties of Ce-TZP-Al nano-composite ceramic, its very low bond strength to esthetic veneers leaves such layered restorations highly susceptible to delamination and chipping under function. Further studies are needed to enhance the surface stability of this high fracture toughness ceramic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 34 publications
0
33
0
3
Order By: Relevance
“…It showed high fracture toughness when compared with Y-TZP 30) . Ce-TZP/Al2O3 is resistant to low-temperature aging degradation 31,32) , while Y-TZP shows lowtemperature degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It showed high fracture toughness when compared with Y-TZP 30) . Ce-TZP/Al2O3 is resistant to low-temperature aging degradation 31,32) , while Y-TZP shows lowtemperature degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were no significant differences between Y-TZP and Ce-TZP/ Al 2O3 with regard to attachment of osteoblasts-like cells in a previous study 33) . Other studies showed superior characteristics for Ce-TZP/Al2O3 when compared with Ti and Y-TZP among common materials for implant body and abutment 32,34) . Regardless of the above advantages, the Ce-TZP/Al2O3 group had samples with bone resorption in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NanoZr contains a higher percentage of Al2O3 (alumina) that replaces part of the zirconia, as compared to the composition of 3Y-TZP materials. Initial tests with Ce-TZP/Al2O3 nanocomposite were very promising, however, other tests did not corroborate the initial data [14][15][16] . The aim of this project was to study the effect of s-LTD (simulated LTD) and thermal fatigue in artificial saliva on the chemical and structural stability of three zirconia-based dental materials.…”
Section: Introductionmentioning
confidence: 92%
“…Zirconia FDPs are feasible for molar region, due to their high flexural strength and fracture toughness [12][13][14][15]. Limited number of clinical studies reported seldom zirconia framework fractures but more often chipping of the veneering ceramic [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%